Dinamika Sosial Ekonomi: Dampak Keberadaan Tambang Batu Bara di Desa Kerta Buana, Kutai Kartanegara - Ummul Khurrin Ain; Mei Vita Romadon Ningrum; Rahmadi Rahmadi; Najma Nur Mawaddah (Universitas Pendidikan Ganesha, 2026)
Coal is a major economic pillar in East Kalimantan, Indonesia and a source of national income. Specifically, Kerta Buana Village is a coal-producing village with mining operations operated by two large mining companies. As a transmigration site, social integration in Kerta Buana Village is formed through a complex process of cultural adaptation. Furthermore, mining exploration in the area around Kerta Buana coincides with the arrival of transmigrants. Based on this background, this study was conducted to analyze the impact of the coal mining industry on the social and economic conditions of the local community around the mine in Kerta Buana Village. This study is a qualitative study with data collection methods conducted through documentation, observation, and interviews. The findings show that the social impacts are reflected in health, education, as well as social and environmental vulnerabilities, while the economic impacts are seen in employment, non-mining economic activities, and infrastructure development. To address these negative impacts, sustainable and responsible mining practices, strict law enforcement, corporate social responsibility programs, and effective environmental rehabilitation are required.